Gender, risk and venture creation intentions - Christopher Dawson; Andrew Henley (Institute for the Study of Labor (IZA), 2012)
This paper is concerned with whether women are less likely to express business start-up intentions because of a less favourable attitude to risk. Previous research suggests that attitude to risk differs significantly between genders, but has not addressed the question of whether this contributes to lower levels of female interest in venture creation. This paper describes a conceptual basis for this question, and investigates it using a survey of business start-up intention from across a sample of European universities. A large proportion of the difference in average levels of intention between genders appears to be associated with attitude to risk.
Keywords: D84; J13; M13; 330; entrepreneurship intentions; attitude to risk; gender difference; Unternehmer; Unternehmensgründung; Geschlecht; Risikopräferenz; Weibliche Führungskräfte; Europa